PENGARUH MODEL PROBLEM-BASED LEARNING TERHADAP KEMAMPUAN NUMERASI DAN SELF-EFFICACY MURID KELAS V DI SD NEGERI 14 TIBAWA - Alfiana Rahman; Masrid Pikoli; Irvin Novita Arifin; Wiwy Trianty Pulukadang; Isnanto Isnanto (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT This study was motivated by the low levels of numeracy skills and self-efficacy among elementary school students, which may hinder success in mathematics learning, particularly in the topic of angle measurement. Numeracy skills and self-efficacy are important aspects that support students’ ability to understand mathematical concepts, solve problems, and develop confidence in learning. This study aimed to determine the effect of the Problem-Based Learning (PBL) model on the numeracy skills and self-efficacy of fifth-grade students at SD Negeri 14 Tibawa. The study employed a quasi-experimental method using a nonequivalent pretest-posttest control group design involving an experimental class and a control class. The research sample consisted of 36 students, with 18 students in the experimental class and 18 students in the control class. Data were collected through a numeracy skills test and a self-efficacy questionnaire and were analyzed using inferential statistics. The results showed that students who participated in learning through the Problem-Based Learning model achieved higher numeracy skills and self-efficacy than those who received conventional instruction. Statistical testing indicated a significant effect of the Problem-Based Learning model on both numeracy skills and self-efficacy, both partially and simultaneously. Therefore, it can be concluded that the Problem-Based Learning model is effective in improving the numeracy skills and self-efficacy of fifth-grade students in mathematics learning at SD Negeri 14 Tibawa. ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya kemampuan numerasi dan self-efficacy murid sekolah dasar yang berpotensi menghambat keberhasilan pembelajaran matematika, khususnya pada materi pengukuran sudut. Kemampuan numerasi dan self-efficacy merupakan aspek penting yang mendukung kemampuan murid dalam memahami konsep matematika, menyelesaikan masalah, serta membangun kepercayaan diri dalam belajar. Penelitian ini bertujuan untuk mengetahui pengaruh model Problem-Based Learning (PBL) terhadap kemampuan numerasi dan self-efficacy murid kelas V di SD Negeri 14 Tibawa. Penelitian ini menggunakan metode kuasi eksperimen dengan desain nonequivalent pretest-posttest control group design yang melibatkan kelas eksperimen dan kelas kontrol. Sampel penelitian berjumlah 36 murid yang terdiri atas 18 murid pada kelas eksperimen dan 18 murid pada kelas kontrol. Data dikumpulkan melalui tes kemampuan numerasi dan angket self-efficacy, kemudian dianalisis menggunakan statistik inferensial. Hasil penelitian menunjukkan bahwa murid yang mengikuti pembelajaran dengan model Problem-Based Learning memperoleh kemampuan numerasi dan self-efficacy yang lebih tinggi dibandingkan murid yang belajar dengan pembelajaran konvensional. Hasil pengujian menunjukkan adanya pengaruh signifikan model Problem-Based Learning terhadap kemampuan numerasi dan self-efficacy, baik secara parsial maupun simultan. Dengan demikian, dapat disimpulkan bahwa model Problem-Based Learning efektif dalam meningkatkan kemampuan numerasi dan self-efficacy murid kelas V pada pembelajaran matematika di SD Negeri 14 Tibawa.